Potential Strategies to Achieve Universal Influenza Vaccination for Children: Provider Attitudes in Two States - Saville, Alison W. (Acad Pediatr, 2018)
OBJECTIVE: Childhood influenza vaccination rates remain suboptimal. Provider perceptions on strategies to achieve universal vaccination are needed. We assessed the perceptions and attitudes of primary care providers across 2 states regarding 2 strategies to potentially bolster rates: centralized reminder/recall (C-R/R), such as reminder/recall (R/R) notices from state immunization registries, and influenza vaccination by complementary community vaccinators (CCVs), such as retail pharmacies, schools, and health departments. METHODS: We sent a mailed survey to a representative sample of providers across Colorado and New York. Questions addressed R/R activities for influenza vaccine, preferences and attitudes about the health department sending C-R/R notices for influenza vaccine, and attitudes about CCVs. Bivariate analyses assessed provider perceptions and compared perceptions by state. RESULTS: The overall response rate was 56% (n = 590/1052). Twenty-two percent of providers in Colorado and 33% in New York performed practice-based R/R for all patients during the 2015–16 influenza season. Eighty-one percent of providers in both states preferred the health department or had no preference for who sent C-R/R notices for influenza vaccine to their patients; most preferred to include their practice names on C-R/R messages. Many providers in both Colorado (75%) and New York (46%, P < .001) agreed that their patients like the option of having CCVs where children can receive influenza vaccine. Some providers expressed concerns regarding potential loss of income and/or difficulty documenting receipt of influenza vaccine at CCVs. CONCLUSIONS: Most providers support C-R/R, and many support CCVs to increase influenza vaccination rates. Collaborations between traditional primary care providers and CCVs might boost coverage.